Adenosine A2A Receptors Control Glutamatergic Synaptic Plasticity in Fast Spiking Interneurons of the Prefrontal Cortex - Kerkhofs, Amber; Canas, Paula M.; Timmerman, A. J.; Heistek, Tim S.; Real, Joana I.; Xavier, Carolina; Cunha, Rodrigo A.; Mansvelder, Huibert D.; Ferreira, Samira G. (Frontiers in Pharmacology, 2018)
Adenosine A2A receptors (A2AR) are activated upon increased synaptic activity to assist in the implementation of long-term plastic changes at synapses. While the involvement of A2AR to control prefrontal cortex (PFC)-dependent behavior such as working memory, reversal learning and effort-based decision making has been reported, it is not known whether A2AR control glutamatergic synapse plasticity within the medial PFC (mPFC). To elucidate that, we tested whether A2AR blockade affects long-term plasticity (LTP) of excitatory postsynaptic potentials (EPSP) in pyramidal neurons and fast spiking interneurons in layer 5 of the mPFC and of population spikes. Our results show that A2AR are enriched at mPFC synapses, where their blockade had no effect on the induction of LTP at excitatory synapses onto layer 5 pyramidal neurons. In contrast, the direction of plasticity at excitatory synapses onto layer 5 fast spiking (FS) interneurons was reversed from LTP to long-term depression (LTD) by blocking A2AR. At the network level, extracellularly induced LTP of population spikes was reduced by A2AR blockade. The interneuron-specificity of A2AR in controlling glutamatergic synapse LTP may ensure that during periods of high synaptic activity, a proper excitation/inhibition balance is maintained within the mPFC.